A efêmera trajetória das escolas normais rurais no Brasil (1930-1970)1 - Chaloba, Rosa Fátima de Souza [UNESP] (Setor de Educação da Universidade Federal do Paraná, 2022)
Between the 1930s and 1970s various experiences in teacher’s training for rural primary schools occured in Brazil, more evidently were the Rural Normal Schools. These experiences were anchored on the moviment towards extending education to the rural areas and within of the principles of New Education and which sought to qualify a teacher apt to work as a agente of civilization in the rural area. This paper analyses the historiography on the theme, pointing out the trends and changes in the conceptions and polices for training rural teachers in Brazil. The study puts into question the brief trajetory of the rural normal schools in Brazil, questioning the meaning of this experience as well as of its failure while stressing the progressive deslocation of the government policies focussed on rural teacher training towards programmes with emphasis on the lay teachers training.

Entre as décadas de 1930 e 1970 ocorreram várias experiências de formação de professores para escolas primárias rurais no Brasil, destacando-se as Escolas Normais Rurais. Essas experiências estiveram ancoradas no movimento pela ruralização do ensino e nos princípios da Escola Nova e pretendiam formar um professor de novo tipo que fosse um agente de civilização do meio rural. Este texto analisa a historiografia sobre o tema assinalando as tendências e mudanças nas concepções e políticas para a formação de professores rurais no país. O estudo põe em questão a breve trajetória das escolas normais rurais no país, interrogando os sentidos dessa experiência e o seu insucesso, assinalando o deslocamento progressivo das políticas governamentais focadas nos professores rurais para programas com ênfase na formação dos professores leigos.
The ephemical trajetory of rural normal schools in Brazil (1930-1970)
Keywords: Rural Normal School; History of teacher training; Rural education; History of teaching profession; Escola Normal Rural; História da formação de professores; Educação rural; História da profissão docente